Designer Extracellular Vesicles Modulate Pro‐Neuronal Cell Responses and Improve Intracranial Retention. Issue 5 (21st January 2022) - Ortega‐Pineda, Lilibeth; Sunyecz, Alec; Salazar‐Puerta, Ana I.; Rincon‐Benavides, Maria Angelica; Alzate‐Correa, Diego; Anaparthi, Amrita Lakshmi; Guilfoyle, Elizabeth; Mezache, Louisa; Struckman, Heather L.; Duarte‐Sanmiguel, Silvia; Deng, Binbin; McComb, David W.; et al.
Abstract: Gene/oligonucleotide therapies have emerged as a promising strategy for the treatment of different neurological conditions. However, current methodologies for the delivery of neurogenic/neurotrophic cargo to brain and nerve tissue are fraught with caveats, including reliance on viral vectors, potential toxicity, and immune/inflammatory responses. Moreover, delivery to the central nervous system is further compounded by the low permeability of the blood brain barrier. Extracellular vesicles (EVs) have emerged as promising delivery vehicles for neurogenic/neurotrophic therapies, overcoming many of the limitations mentioned above. However, the manufacturing processes used for therapeutic EVs remain poorly understood. Here, we conducted a detailed study of the manufacturing process of neurogenic EVs by characterizing the nature of cargo and surface decoration, as well as the transfer dynamics across donor cells, EVs, and recipient cells. Neurogenic EVs loaded with  Ascl1,   Brn2, and  Myt1l  ( ABM ) are found to show enhanced neuron‐specific tropism, modulate electrophysiological activity in neuronal cultures, and drive pro‐neurogenic conversions/reprogramming. Moreover, murine studies demonstrate that surface decoration with glutamate receptors appears to mediate enhanced EV delivery to the brain. Altogether, the results indicate that  ABM‐ loaded designer EVs can be a promising platform nanotechnology to drive pro‐neuronal responses, and that surface functionalization with glutamate receptors can facilitate the deployment of EVs to the brain. Abstract : Designer extracellular vesicles (EVs) are manufactured via non‐viral engineering of donor cells through electroporation. Designer EVs are packed with plasmid DNA, mRNA, and protein content. Transfecting donor cells with expression plasmids for membrane proteins can be used to tailor the surface decoration of the EVs. Pro‐neurogenic designer EVs drive neurogenesis and improve targeting of neuronal tissue, in vitro and in vivo.